Sevoflurane Postconditioning Attenuates Hypoxia/Reoxygenation Injury of Cardiomyocytes Under High Glucose by Regulating HIF-1α/MIF/AMPK Pathway - Ma, Haiping; Li, Yongjie; Hou, Tianliang; Li, Jing; Yang, Long; Guo, Hai; Li, Lili; Xin, Mingxiu; Gong, Zhongcheng (Frontiers in Pharmacology, 2021)
Subject: Cardiovascular disease, as the most common and serious coexisting disease in diabetic patients, is far more harmful than diabetes itself, and is one of the risk factors that seriously affect the prognosis and complications of surgical patients. Previous studies have shown that sevoflurane post-conditioning (SpostC) exerts a protective effect against myocardial ischemia/reperfusion injury by HIF-1α, but the protective effect is weakened or even disappeared under hyperglycemia. This study aims to explore whether regulating the HIF-1α/MIF/AMPK signaling pathway can restore the protective effect and reveal the mechanism of SpostC on cardiomyocyte hypoxia/reoxygenation injury under high glucose conditions. Methods: H9c2 cardiomyocytes were cultured in normal and high-concentration glucose medium to establish a hypoxia/reoxygenation (H/R) injury model of cardiomyocytes. SpostC was performed with 2.4 % sevoflurane for 15 minutes before reoxygenation. Cell damage was determined by measuring cell viability, lactate dehydrogenase activity, and apoptosis; testing cell energy metabolism by detecting reactive oxygen species (ROS) generation, ATP content and mitochondrial membrane potential; Western blotting was used to examine the expression of HIF-1α, MIF, and AMPK proteins. HIF-1α and MIF inhibitors and agonists were administered 40 minutes before hypoxia. Results: 1. SpostC exerts a protective effect by increasing cell viability, reducing LDH levels and cell apoptosis under low glucose (5 μM) after undergoing H/R injury ; 2. High glucose concentration (35 μM) eliminated the cardioprotective effect of SpostC, which is manifested by a significantly decrease in the protein expression level of the HIF-1α/MIF/AMPK signaling pathway, accompanied by decreased cell viability, increased LDH levels and apoptosis, increased ROS production, decreased ATP synthesis, and decreased mitochondrial membrane potential; 3. Under high glucose (35 μM) , the expression levels of HIF-1α and MIF were up-regulated by using agonists and the cardioprotective effect of SpostC was restored. Conclusion: The signal pathway of HIF-1α/MIF/AMPK of H9c2 cardiomyocytes may be the key point of SpostC against H/R injure after undergoing H/R injury. The cardioprotective of SpostC could be restored by upregulating the protein expression of HIF-1α and MIF.